Magnetic and Dielectric Study of Ceramic Nanocomposite Nickel Ferrite and Barium Titanate Compounds. (8th November 2021) - Mahalakshmi, S.; Swetha, S.; Nithiyanatham, S.; Jayasri, R; Santhi, K.
Abstract : Owing to high dielectric constants and coupled magnetic properties at room temperature, multiferroics related materials have wide application in many fields like multi-layer ferroic capacitors and multifunctional devices. Nickel ferrite, barium titanate composite is prepared from co-precipitation method and sintered at high temperature (1273 K). Intrinsic stretching vibrations observed in FTIR spectra at 594 cm −1 . X-ray measurements detected the presence of their single phases (tetragonal perovskite crystal). Variations of AC dielectric constant in these samples have been studied. The influence of the phase content on the dielectric constant and loss tangent conductivity was also studied. The AC measurement yields smaller variations at a low range of frequency and more variations in higher frequency ranges indicate amplification of confined states with the availability of large charge carriers. A magnetic measurement reveals that the soft ferromagnetic properties of 68.356 emu g −1 and 20.465 emu g −1 at room temperature.